A RARE CASE OF MECKEL’S DIVERTICULUM STRANGULATION COMPLICATED BY SMALL INTESTINE OBSTRUCTION (CLINICAL CASE) - Kravets, Oleksandr; Svistunov, Oleksandr; Moskalenko, Roman (Eastern Ukrainian Medical Journal, 2024)
Introduction. Meckel’s diverticulum (MD) is a congenital anomaly of the gastrointestinal tract. In most cases, uncomplicated DM is silent. It is mainly diagnosed when complications arise or accidentally during diagnostic procedures or surgical interventions. A recognised effective diagnostic method is laparoscopy, which allows to assess the localisation and degree of pathological changes in the diverticulum. Treatment of complicated DM is surgical. The volume of surgery depends on the diameter of the diverticulum, the nature of complications, the prevalence of the inflammatory process at the base of the diverticulum and the ileum wall, and the spread of peritonitis. In this report, we would like to share our own successful experience of treating a patient with DM complicated by necrosis and volvulus of the small intestine. Case report. A 42-year-old male patient was hospitalised with complaints of abdominal pain, fever up to 38°C, and nausea. During the examination, the abdomen was distended, painful in all parts, spared during breathing. In the right iliac region and in the right lateral canal, there were weakly positive symptoms of peritoneal irritation, peristalsis was weakened. Ultrasound examination of the abdominal cavity revealed free fluid in the right hypochondrium and pelvic cavity, dilatation of the small intestine loops. Plain radiography of the abdominal cavity: pneumatosis of the intestine, small intestinal fluid levels. Video laparoscopy was performed to clarify the diagnosis under endotracheal anaesthesia. During the revision of the abdominal cavity, a defect of up to 5.0 cm in the mesentery of the small intestine with a large-sized and necrotic altered DM and a wrap around it of small intestinal loops with necrosis was detected. Resection of the necrotic loops of the small intestine with DM was performed with the application of a «side-to-side» intestinal anastomosis. The postoperative period was uneventful. The patient was discharged on day 10. Discussion. Due to the lack of characteristic symptoms, the diagnosis of DM, even in cases of complications, is sometimes established late, which entails problems in the further treatment of patients. Today, laparoscopy is the leading and most informative method in the diagnosis of DM. In some cases, it is the first stage of surgical intervention. Intestinal obstruction is one of the most common complications of DM. It is caused by small intestine torsion around a fixed diverticulum, nodule formation, and diverticulum invasion. Early diagnosis is important because delayed surgery increases mortality. We present a clinical case of complicated DM with symptoms typical of small bowel obstruction. The standard methods used at the first stage of diagnosis did not allow to establish the cause of intestinal obstruction. Only the use of laparoscopy made it possible to establish an accurate diagnosis. To date, the question of the need to remove an accidentally found DM remains unresolved. It is believed that an individual approach is advisable. In cases of complications, the choice of surgical intervention depends on the diameter of the diverticulum base, the severity of morphological changes in its wall and the wall of the small intestine. Conclusions. The absence of specific symptoms and low informational content of routine diagnostic methods are the reason for the untimely diagnosis of DM, which often causes the development of severe complications. Laparoscopy is the only significant diagnostic and treatment method that allows for an accurate diagnosis and, in some cases, diverticulectomy. An individual approach is recommended in the treatment of DM, depending on the clinical situation.